SUSCEPTIBILITY AND RISKS TO WATER EROSION IN THE UPPER OF ARAGUAIA RIVER BASIN (GO/MT), BRAZIL - OLIVEIRA, Victoria Christina Vilela; CASTRO, Selma Simões de (Sociedade & Natureza)
The soil is a very important natural resource to life in general, especially to human life, because it is the base of its activities. However, in some parts of the word it is not exposed to adequate conservational practices, which result in degradation of the quality and negative impacts on the ecosystems and biodiversity. One of this impacts concerns the water erosion, the most important cause of the accelerated loss of properties on agricultural lands by reduction of fertility, desertification and increase of recent sedimentation in the hydrical channels. The laminar erosion is a common form but no evident signs are visible, except when the roots appear on the cultures and pastures. It is caused by runoff, mainly in the tropics.Some soils have high susceptibility and risks to this form of erosion, frequently the fine sandy soils after deforestation of their original cover and replacement by intensive agricultural an pasturage activities without conservational practices.